Ten year radiation budget of the Earth: 1984-93 - Hatzianastassiou, N.; Matsoukas, C.; Hatzidimitriou, D.; Pavlakis, C.; Drakakis, M.; Vardavas, I. (2004)
A 10 year (1984-93) climatology is given of the global distributions of net shortwave (SW), net longwave (LW) and net all-wave radiation budget at both top-of-atmosphere (TOA) and at the Earth's surface, on a mean monthly basis, computed with a radiative transfer model with input data for key atmospheric and surface parameters. The model input data were taken from complete and comprehensive global climatological data sets, such as the International Satellite Cloud Climatology Project, the National Centers for Environmental Prediction and National Center for Atmospheric Research Global Reanalysis or the TIROS Operational Vertical Sounder, among others. Seasonal and latitudinal variations and mean annual and mean hemispherical and global averages are given, based on model results computed for each month of the period from January 1984 to December 1993. At TOA, the net incoming SW radiation has larger latitudinal variation and range of values (0-400 W m-2) than the outgoing LW radiation (100-350 W m-2). At the surface, the net downward SW radiation has similar features to that at TOA, but with smaller magnitudes. The net upward LW radiation is quite different than at TOA, with a smaller seasonal and geographical variability than the surface net SW radiation. The global system of Earth-atmosphere is found to be net radiatively heated at TOA by 3 W m-2; the Earth's surface is net heated by 98 W m-2, mainly due to solar absorption equal to 147 W m-2, a value in agreement with surface-based measurements. At TOA, there is a radiative energy surplus between 40 °S and 30 °N and a radiative loss poleward; however, at the surface the surplus regions extend from 70 °S to 70 °N. Globally, the atmosphere is found to absorb 27% of the incoming solar radiation at TOA, while it emits 79% of the outgoing terrestrial radiation.
Keywords: all-wave; budget; Climatology; global; longwave; Modelling; Radiation; shortwave